Документальні колекції інституту президентства країн світу: специфіка представлення - Дем’яненко, Л. Г. (My University, 2015)
У статті розкрито специфіку представлення та надання доступу до документальних колекцій інституту президентства в спеціалізованих установах країн світу. Віртуальне представлення президентських бібліотек світу розглядається як результат розвитку інноваційних технологій, які активно впроваджуються у діяльність бібліотек, фондів, архівів, музеїв.

The paper deals with the peculiarities of the presentation and access to the documental collection of presidency in the special institution all over the world. The web-presentation of the presidential libraries is reviewed as the result of innovative technologies development, which is put into practice of libraries, collections archives and museums actively.
The documental collection of the presidency around the world: specificity of presentation
Keywords: "Фонд Президентів України"; "Фонд Президентов Украины"; архивно-библиотечный фонд; архівно-бібліотечний фонд; електронні ресурси; электронные ресурсы; музейный фонд; музейний фонд; президентська бібліотека; президентская библиотека; presidential libraries; archival and library collection; museum collection; electronic resources; the Collection of the Presidents of Ukraine